Chironomids’ Relationship with Aeromonas Species - Laviad, Sivan; Halpern, Malka (Frontiers in Microbiology, 2016)
Chironomids (Diptera: Chironomidae), also known as non-biting midges, are one of the most abundant groups of insects in aquatic habitats. They undergo a complete metamorphosis of four life stages of which three are aquatic (egg, larva, pupa), and the adult emerges into the air. Chironomids serve as a natural reservoir of Aeromonas and Vibrio cholerae species. Here we review existing knowledge about the mutual relations between Aeromonas species and chironomids. Using 454-pyrosequencing of the 16S rRNA gene, we found that the prevalence of Aeromonas species in the insects’ egg masses and larvae was 1.6% and 3.3% of the insects’ endogenous microbiota, respectively. Aeromonas abundance per egg mass remained stable during a six-month period of bacterial monitoring. Different Aeromonas species were isolated and some demonstrated the ability to degrade the insect’s egg masses and to prevent eggs hatching. Chitinase was identified as the enzyme responsible for the egg mass degradation. Different Aeromonas species isolated from chironomids demonstrated the potential to protect their host from toxic metals. Aeromonas is a causative agent of fish infections. Fish are frequently recorded as feeding on chironomids. Thus, fish might be infected with Aeromonas species via chironomid consumption. Aeromonas strains are also responsible for causing gastroenteritis and wound infections in humans. Different virulence genes were identified in Aeromonas species isolated from chironomids. Chironomids may infest drinking water reservoirs, hence be the source of pathogenic Aeromonas strains in drinking water. Chironomids and Aeromonas species have a complicated mutual relationship.